Prospective study of the long-term outcomes and complications after total temporomandibular joint replacement: analysis at 10 years. Issue 5 (May 2022) - Rajkumar, A.; Sidebottom, A.J.
Abstract: This prospective analysis was performed to assess the long-term benefits of the TMJ Concepts joint replacement system in the UK. All patients who had replacement temporomandibular joints (TMJ) with at least 10 years of follow-up were included. The most common primary diagnoses were trauma, multiple previous operations, psoriatic arthritis, rheumatoid arthritis, degenerative disease, and ankylosis. A total of 43 patients (62 joints) were followed up for 10 years (mean age 45, range 22–70 years); 39 were female and four were male. The mean number of previous TMJ procedures was 2.5 (range 0–10). Over the 10 years of follow-up, there were significant improvements in pain score (10-point scale; decreased from 7.4 to 1.7), maximum mouth opening (increased from 21.0 mm to 34.7 mm), and dietary score (10-point scale; increased from 4.1 to 9.5). Joints in two patients failed, one secondary to a local dental infection and one due to reankylosis. None failed due to wear of the prosthesis, whether the prosthesis was standard cobalt–chrome or all-titanium. Total TMJ replacement gives good long-term improvements, both lessening pain and improving function, and is an effective form of management for irreparably damaged joints.